Aorto‐Mesenteric and Renal Allograft Transplant: A Novel Treatment for Midaortic Syndrome. Issue 4 (22nd February 2013) - Vakili, K.; Fullington, N. M.; Turner, C. G.; Cauley, R. P.; Potanos, K. M.; Lee, S.; Ferguson, M.; Lock, J. E.; Kim, H. B.
<x xml:space="preserve">Abstract</x> Midaortic syndrome (MAS) is a rare condition characterized by stenosis of the aorta and often involving renal and visceral arteries. Current therapies include medical management of associated hypertension, and interventional procedures such as angioplasty or surgical bypass. We report a 2‐year‐old female with severe MAS who was initially treated with angioplasty and stents in both her aorta and superior mesenteric artery (SMA). Due to the presence of long segment stenoses, her renal arteries were not amenable to surgical reconstruction and she rapidly progressed to Stage V chronic kidney disease. The patient underwent bilateral nephrectomy and renal transplantation using a donor thoracoabdominal aorta allograft to provide inflow for the kidney as well as to bypass the nearly occluded aorta. The donor SMA was used to bypass the native SMA stenosis. Postoperatively, the patient had normalization of four limb blood pressures. She weaned from five anti‐hypertensive agents to monotherapy with excellent renal function. This is the first reported case of thoracoabdominal aortic bypass using allograft aorta to address MAS. This approach allowed for successful kidney transplantation with revascularization of the mesenteric, and distal aortic circulation using allograft conduit that will grow with the child, obviating the need for repeated interventional or surgical procedures.